2020
DOI: 10.1016/j.jcv.2020.104548
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of tenofovir resistance in chronic hepatitis B virus (HBV) infection: An observational case series of South African adults

Abstract: Introduction Tenofovir disoproxil fumarate (TDF) is widely recommended for treatment of chronic hepatitis B virus (HBV) infection because it is safe, affordable and has a high genetic barrier to resistance. TDF resistance associated mutations (RAMs) have been reported, but data are limited, particularly for Africa. We set out to identify potential RAMs in individuals with detectable HBV viraemia on TDF treatment. Methods We recruited adults with chronic HBV infection fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Emerging reports suggest that RT polymorphisms can be associated with reduced TDF susceptibility [ 41 ]. Among these, L217R was present as consensus in sample 118 (55 % of reads) and V191I was identified as a minority variant (28 % reads) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Emerging reports suggest that RT polymorphisms can be associated with reduced TDF susceptibility [ 41 ]. Among these, L217R was present as consensus in sample 118 (55 % of reads) and V191I was identified as a minority variant (28 % reads) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…TAF also demonstrates broad cross-genotype activity against wild-type HBV clinical isolates and is effective against multidrug-resistant HBV isolates in vitro ( 23 ). Despite high genetic barriers to TFV, emerging evidence has reported that extensive amino acid substitutions were associated with reduced TFV sensitivity, described in both treatment- naïve and -experienced individuals with CHB ( 6 , 8 , 10 ) in Asia, Africa, and Europe. Moreover, in a clinical setting, 0.8–24% patients exhibited a partial response to TDF, while some developed viral breakthrough despite good adherence to TDF ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several problems are increasingly emerging with long-term antiviral therapy. First, drug resistance is gradually increasing, including resistance to ETV and TDF (5)(6)(7)(8)(9)(10). Second, a diminished estimated glomerular filtration rate, hypophosphatemia, hyperphosphaturia, and Fanconi syndrome have been reported in patients using TDF (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from Korea demonstrated TDF‐resistant HBV mutants in a treatment‐naïve patient 73 as well as two patients who had previously developed virological breakthrough during mono‐ and combination therapy with other NAs 74 . Furthermore, a recent case series of 66 African patients with CHB suggested possible TDF resistance in three patients including two patients coinfected with HIV 75 . The emergence of TDF‐resistant HBV mutants following short‐term TDF exposure in consecutive pregnancies is unclear but predicted to be extremely rare 24 …”
Section: Virological Response To Tdf and Tolerability Of Tdf In Pregn...mentioning
confidence: 99%
“…74 Furthermore, a recent case series of 66 African patients with CHB suggested possible TDF resistance in three patients including two patients coinfected with HIV. 75 The emergence of TDF-resistant HBV mutants following short-term TDF exposure in consecutive pregnancies is unclear but predicted to be extremely rare. 24 All studies that assessed antiviral potency of TDF in pregnant patients with CHB demonstrated that TDF is associated with a reduction in HBV-DNA levels at delivery versus baseline, 17 ,18,20,21,29,32-39,76 even in pregnant CHB patients resistant to LAM or LdT.…”
Section: Virolog I C Al Re S P On S E To Tdf and Toler Ab Ilit Y Of T...mentioning
confidence: 99%